Primary Laryngeal Blastomycosis: Diagnostic Challenges and Advances in a Rare Cause of Laryngitis. (23rd May 2019) - Cates, Daniel J.; Rosen, Clark A.; Yassin, Mohamed H.; Smith, Libby J.
Abstract : Blastomyces dermatitidis is a fungal organism endemic to the central and southern United States and capable of causing numerous diseases. Primary blastomycosis of the larynx is a rare clinical entity with a limited number of reported cases in the literature. Diagnosis is challenging as a result of nonspecific physical exam findings, difficulty of histopathologic detection and culture, and need for operative laryngeal biopsy for definitive identification. Molecular and serologic testing is not widely available. The authors present a case of laryngeal blastomycosis, the diagnosis of which was facilitated by in‐office biopsy, and discuss diagnostic challenges. Laryngoscope, 129:2531–2533, 2019